High-level architecture for a digital oilfield: features of the transition to data-driven decision management; IOP Conference Series: Materials Science and Engineering; Vol. 1019 : 14th International Forum on Strategic Technology (IFOST 2019) - Savelyev A. O. Aleksey Olegovich (2021, 2021)
Title screen